0

just started logic, and I cannot seem to know know to solve this assigment. I've tried this:

I've tried this

I suspect I cannot break the disjunction on P, only with A hypotesis. How should I split it?

Thank you

4
  • $A\implies C $ is equivalent with $\neg A\ lor C$ so we get $(\neg A\lor C ) \lor (\neg A\lor D)$ hence $\neg A \lor (C\lor D)$ so $A\implies (C\lor D)$ – user47436 Sep 21 '20 at 10:08
  • 2
    The fist step is to apply Disjunction-elim to the premise and then the two sub-proofs assuming A. – Mauro ALLEGRANZA Sep 21 '20 at 10:26
  • @HassanJolany - there is no math formula processor on PhilSE. – Mauro ALLEGRANZA Sep 21 '20 at 10:54
  • I'll look at your suggestions. Thank you both. – SimpleOne Sep 21 '20 at 20:09
1

You need to resolve each of the cases into the term you want to proof to be able to use a disjunction elimination, like so: enter image description here

1
  • I also tried to solve the subproof A->C, etc. but it didn't occur to me to nest another subproof for that. Now it looks so simple. Thanks for the complete answer. I know the socratic method is usually best to get a good understanding, but in my case I needed this step-by-step guide. – SimpleOne Sep 26 '20 at 21:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.